Acktive Paking for Food Apllications - Aaron L. Brody (CRC PRESS, 2001)
ACTIVE packaging, sometimes referred to as interactive or â€œsmartâ€ packaging, is intended to sense internal or external environmental change and to respond by changing its own properties or attributes and hence the internal package environment. Active packaging has been considered a component of the packaging discipline for several decades or since the first inclusion of desiccants in dry product packages. In their own moisture-permeable sachets, desiccants absorb water vapor from the contained product and from the package headspace, and absorb any water vapor that enters by permeation or transmission through the package structure. As separate entities within packages, active packaging sachets, pouches, patches, coupons, labels, etc., are not often integral to the packageâ€”a semantic differentiation.